Storage and transformation of organic matter fractions in cryoturbated permafrost soils across the Siberian Arctic - Gentsch, Norman; Mikutta, Robert; Alves, Ricardo J. Eloy; Barta, Jin; Čapek, Petr; Gittel, Antje; Hugelius, Gustaf; Kuhry, Peter; Lashchinskiy, Nikolay; Palmtag, Juri; Richter, Andreas; Šantrůčková, Hana; et al. (Göttingen : Copernicus, 2015)
In permafrost soils, the temperature regime and the resulting cryogenic processes are important determinants of the storage of organic carbon (OC) and its small-scale spatial variability. For cryoturbated soils, there is a lack of research assessing pedon-scale heterogeneity in OC stocks and the transformation of functionally different organic matter (OM) fractions, such as particulate and mineral-associated OM. Therefore, pedons of 28 Turbels were sampled in 5 m wide soil trenches across the Siberian Arctic to calculate OC and total nitrogen (TN) stocks based on digital profile mapping. Density fractionation of soil samples was performed to distinguish between particulate OM (light fraction, LF, < 1.6 g cm−3), mineral associated OM (heavy fraction, HF, > 1.6 g cm−3), and a mobilizable dissolved pool (mobilizable fraction, MoF). Across all investigated soil profiles, the total OC storage was 20.2 ± 8.0 kg m−2 (mean ± SD) to 100 cm soil depth. Fifty-four percent of this OC was located in the horizons of the active layer (annual summer thawing layer), showing evidence of cryoturbation, and another 35 % was present in the upper permafrost. The HF-OC dominated the overall OC stocks (55 %), followed by LF-OC (19 % in mineral and 13 % in organic horizons). During fractionation, approximately 13 % of the OC was released as MoF, which likely represents a readily bioavailable OM pool. Cryogenic activity in combination with cold and wet conditions was the principle mechanism through which large OC stocks were sequestered in the subsoil (16.4 ± 8.1 kg m−2; all mineral B, C, and permafrost horizons). Approximately 22 % of the subsoil OC stock can be attributed to LF material subducted by cryoturbation, whereas migration of soluble OM along freezing gradients appeared to be the principle source of the dominant HF (63 %) in the subsoil. Despite the unfavourable abiotic conditions, low C / N ratios and high δ13C values indicated substantial microbial OM transformation in the subsoil, but this was not reflected in altered ...